Adnexal torsion in adolescents. Issue 5 (October 2015) - Spinelli, Claudio; Piscioneri, Jessica; Strambi, Silvia
<x xml:space="preserve">Abstract</x> Purpose of review Adnexal torsion is a surgical emergency, which requires immediate recognition and prompt treatment. This article aims to systematically illustrate the most relevant approach to follow in cases of suspected adnexal torsion in adolescents. We based our evaluation of the role of clinical features, laboratory tests, and imaging on recent literature, till we consider the most appropriate surgical treatment. Recent findings The literature describes the conservative treatment for adnexal torsion, consisting of detorsion, as the best surgical approach to guarantee the future reproductive capacity of patients. Recent experimental studies have focused on the consequences of detorsion, which may cause ischemia-reperfusion damage and have speculated about the role of different drugs for its avoidance. Summary A systematic review of physiopathology, clinical picture, and imaging of adnexal torsion is certainly useful to identify as soon as possible this emergency condition. An early identification and an adequate treatment are indispensable in order to achieve a proper outcome for the patient. The choice of the appropriate surgical approach can be challenging and should be made on the basis of an accurate evaluation of the ovarian lesion. Therefore, it would be useful to perform an intraoperative frozen section analysis in selected cases.